'Welcome to the civilization of fear': on political graffiti heterotopias in Greece in times of crisis. (November 2015) - Zaimakis, Yiannis
Drawing upon ethnographical research carried out in Greek cities, this article discusses the use of political graffiti as a creative, playful response to the economic depression, social upheavals and precariousness surrounding the writers and as an act of civil disobedience and political protest in the context of the Greek economic crisis. The graffiti creation releases a flood of cultural responses to the crisis and gives an insight into the lived experience endured by the Greek people faced with the gloomy conditions of a society in crisis. The analysis traces the ways in which activists and unaligned writers turn their attention to the creative and expressive potential of graffiti and articulate cultural heterotopias on the visual landscape of Greek cities. Spatial politics allow distinctive political voices to transform the material dimensions of urban life in meaningful visual expression. The act of doing graffiti in the dystopia of crisis shows the desire of grassroots artists and cultural activists to use their creative capacities to overcome the unfavourable material conditions of their existence and to build alternative counter-hegemonic spaces of representation in the urban landscapes, challenging austerity policies and the existing social order.